Preparation method of porous negative electrode material derived from high silicon slag

Through the liquid-solid reaction and alkali-soluble calcining process of high silicon slag and quaternary ammonium alkali, porous carbon silicon materials were prepared, which solved the problems of poor conductivity and large volume expansion of existing silicon materials, and achieved excellent electrochemical performance and low-cost process of the negative electrode material.

CN119841320AActive Publication Date: 2025-04-18YIDU XINGFA CHEMICAL CO LTD
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
CN202411762584.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-03
Publication Date
2025-04-18
Estimated Expiration
2044-12-03

AI Technical Summary

Technical Problem

When existing silicon materials are used in lithium-ion battery negative electrode materials, poor conductivity and large volume expansion limit their application, and the existing processes are complex and costly.

Method used

A mixture of high silicon slag and quaternary ammonium alkali is used to carry out liquid-solid reaction, and porous carbon silicon material is prepared through alkali-soluble calcining process, which is used for the preparation of negative electrode materials.

Benefits of technology

The prepared negative electrode material has excellent electrochemical properties, good stability, simple process and low cost, achieving high-value utilization of silicon slag.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The invention relates to a preparation method of a porous negative electrode material derived from high-silicon slag, which comprises the following steps of: (1) mixing the high-silicon slag with an organic substance to react; (2) filtering after the reaction is finished, and taking filtrate; (3) evaporating and crystallizing the filtrate; and (4) calcining the crystallized product to prepare the silicon negative electrode material. The high-silicon slag is used as the raw material to prepare the negative electrode material, the electrochemical performance is excellent, the production cost is greatly reduced, the problems of stockpiling and the like of the high-silicon slag are solved while the economic benefits of enterprises are improved, the high-value utilization of the high-silicon slag is realized, and the sustainable development strategy is met.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of chemistry, and in particular relates to a method for preparing a porous negative electrode material derived from high-silicon slag. Background Art

[0002] Phosphorus chemical companies produce a large amount of high-silicon slag as a by-product, the main component of which is silicon dioxide, followed by calcium oxide, and contains a small amount of aluminum oxide and iron oxide. The main way to dispose of high-silicon slag is to mix it with cement for the preparation of retarders, or to prepare hollow bricks and other building materials. The utilization method is relatively low-value. With the increasing attention paid to environmental protection and resource recycling, the high-value-added utilization of high-silicon slag has become an industry pain point that needs to be solved urgently.

[0003] Silicon materials are considered to be an ideal choice for the negative electrode materials of the next generation of lithium-ion batteries due to their advantages such as high capacity and low cost, but their poor conductivity and large volume expansion limit their application. Patent CN117894968B uses gelatin as a carbon source, and constructs a continuous conductive network on the surface of silicon powder through wet coating and pyrolysis processes to prepare silicon-carbon materials with excellent cycle performance and rate performance. However, the silicon-carbon materials prepared by this method have a solid coating layer that is easy to separate, a complex preparation process, and high cost. Based on this, this patent proposes a silicon slag-derived porous negative electrode material with a simple low-cost process flow and excellent electrochemical performance, and a preparation method thereof. Summary of the invention

[0004] In order to solve the above problems, the present invention aims to provide a method for preparing porous negative electrode materials derived from high-silicon slag, so as to prepare negative electrode materials with excellent electrochemical properties; while satisfying the requirements of simple manufacturing process and low cost, high-value utilization of silicon slag is achieved.

[0005] The technical solution of the present invention is as follows: A method for preparing a porous negative electrode material derived from high-silicon slag, the method comprising the following steps: (1) Mix high silicon slag and organic matter in a certain liquid-solid ratio in a solution and react at a certain temperature: (2) After the reaction is completed, filter and take the filtrate; (3) Evaporating and crystallizing the filtrate; (4) The crystalline product is calcined to prepare a silicon-based negative electrode material.

[0006] Preferably, the high silicon slag composition is: silicon dioxide 68%-69%, silicate 15.5%-16.5%, basic calcium phosphate dihydrate 14.5%-15.5%, potassium fluoride 0.5%-1%.

[0007] Preferably, the high silicon slag is first pickled, and the pickling solution includes a mixture of one or more of nitric acid, hydrochloric acid and sulfuric acid. The mass concentration of the pickling solution is 30-50%. During the pickling process, the liquid-to-solid ratio is 1:1.

[0008] Preferably, the organic substance is a quaternary ammonium base mixture. The presence of the organic base can obtain organic silicon with higher purity, thereby preparing a negative electrode material with excellent electrochemical performance.

[0009] Further preferably, the quaternary ammonium base mixed material is: tetramethylammonium hydroxide:tetraethylammonium hydroxide:tetrabutylammonium hydroxide = 1:1:1.

[0010] Preferably, in step (1), the molar ratio of the quaternary ammonium base to silicon is (1.8-3):1, the reaction temperature is 50°C-100°C, the liquid-solid ratio is 5-20, and more preferably, the liquid-solid ratio is 8-10.

[0011] Further preferably, the molar mass ratio of the total molar amount of the quaternary ammonium mixture to the molar mass ratio of silicon in the silicon slag is (2-2.5):1.

[0012] Further preferably, the molar ratio of tetramethylammonium hydroxide, tetraethylammonium hydroxide and tetrabutylammonium hydroxide in the quaternary ammonium base mixture in step (1) is (0.1-2): (0.1-2): (0.1-2), preferably, the molar ratio of tetramethylammonium hydroxide, tetraethylammonium hydroxide and tetrabutylammonium hydroxide is 1:1:1, and the addition ratio of polyethylene glycol is 0.1%-0.2% of the total mass of the high silicon slag and the quaternary ammonium base mixture. .

[0013] Further preferably, the liquid-to-solid ratio in step (1) is 8-10, and the reaction temperature is 70-100°C.

[0014] Preferably, the reaction time of step (2) is 1-3 h.

[0015] Further optimization, the drying method described in step (3) is freeze-drying.

[0016] Preferably, the calcination atmosphere in step (4) is nitrogen, the calcination temperature is 700° C.-1000° C., and the calcination time is 1.5-2 h.

[0017] Compared with the prior art, the present invention has the following beneficial effects: (1) The present invention uses silicon slag as raw material and prepares a porous carbon silicon material with high purity through alkali dissolution and calcination. The material is used for the preparation of negative electrode materials and can give them excellent electrochemical properties.

[0018] (2) During the process, the organic base can combine with the silicon material through chemical bonds. After calcination, the silicon is firmly fixed in the carbon material structure, so that the prepared negative electrode material has good stability.

[0019] (3) The quaternary ammonium base in the present invention adopts a variety of material ratios, which can optimize the pore size distribution in the carbon framework after calcination and improve the electrochemical performance.

[0020] (4) The present invention uses silicon slag as raw material, and the addition of organic base can accurately purify the silicon element. At the same time, the organic base material generates porous carbon after calcination, which can improve the electrochemical properties of the material.

[0021] (5) The overall preparation process is simple to operate and can achieve high-value utilization of silicon slag, which is environmentally friendly and at the same time achieves high-value utilization of silicon slag. DETAILED DESCRIPTION

[0022] The following will be combined with the specific embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. The embodiments described are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work belong to the protection scope of the present invention.

[0023] In order to better illustrate the above implementation scheme, the following examples are listed. The scope of the present invention is not limited to the examples listed. The silicon slag used in the examples is produced by Yidu Xingfa Chemical Co., Ltd., and its composition is 68%-69% silicon dioxide, 15.5%-16.5% silicate, 14.5%-15.5% basic calcium phosphate dihydrate, and 0.5%-1% potassium fluoride.

[0024] The quaternary ammonium base mixture used in the embodiment is a mixture of tetramethylammonium hydroxide, tetraethylammonium hydroxide, and tetrabutylammonium hydroxide in a ratio of 1:1:1.

[0025] Example 1 Soak the high silicon slag in a mixture of sulfuric acid and nitric acid (1:1) at a liquid-solid ratio of 50% for 5 hours, filter and dry, weigh the silicon slag and quaternary ammonium alkali mixture according to the molar mass ratio of alkali to silicon of 2:1. Place it in an aqueous solution at a liquid-solid ratio of 8:1, raise the temperature to 70°C, react for 2 hours, filter, distill and dry the filtrate, place the dried solid in a tubular furnace under a nitrogen atmosphere, heat at 800°C for 1.5 hours, and finally take out the calcined solid.

[0026] Example 2 Soak high silicon slag in a mixture of sulfuric acid and nitric acid (3:1) at a liquid-to-solid ratio of 50% for 5 hours, filter and dry, weigh silicon slag and quaternary ammonium base mixture according to the molar mass ratio of alkali to silicon of 2:1, place it in an aqueous solution at a liquid-to-solid ratio of 9:1, raise the temperature to 80°C, react for 2.5 hours, filter, distill and dry the filtrate, place the dried solid in a tubular furnace under a nitrogen atmosphere, heat at 850°C for 2 hours, and finally take out the calcined solid.

[0027] Example 3 The high silicon slag was soaked in a mixture of sulfuric acid and nitric acid (3:1) at a liquid-to-solid ratio of 50% for 5 hours, filtered and dried, and the silicon slag and quaternary ammonium base mixture were weighed according to the molar mass ratio of alkali to silicon of 2.4:1, and placed in an aqueous solution at a liquid-to-solid ratio of 10:1. The temperature was raised to 90°C, reacted for 3 hours, filtered, and the filtrate was distilled and dried. The dried solid was placed in a tubular furnace under a nitrogen atmosphere and heated at 900°C for 2 hours. Finally, the calcined solid was taken out.

[0028] Example 4 The high silicon slag was soaked in a mixture of hydrochloric acid and nitric acid (3:1) at a liquid-to-solid ratio of 50% for 6 hours, filtered and dried, and the silicon slag and quaternary ammonium base mixture were weighed according to a molar mass ratio of alkali to silicon of 2.5:1, and placed in an aqueous solution at a liquid-to-solid ratio of 10:1. The temperature was raised to 100°C, reacted for 3 hours, filtered, and the filtrate was distilled and dried. The dried solid was placed in a tubular furnace under a nitrogen atmosphere and heated at 1000°C for 2 hours. Finally, the calcined solid was taken out.

[0029] Example 5 Soak high silicon slag in a mixture of hydrochloric acid and nitric acid (1:1) at a liquid-to-solid ratio of 50% for 8 hours, filter and dry, weigh silicon slag and quaternary ammonium base mixture according to a molar mass ratio of alkali to silicon of 2.5:1, place it in an aqueous solution at a liquid-to-solid ratio of 10:1, raise the temperature to 100°C, react for 3 hours, filter, distill and dry the filtrate, place the dried solid in a tubular furnace under a nitrogen atmosphere, heat at 1100°C for 2 hours, and finally take out the calcined solid.

[0030] Example 6 The high silicon slag was soaked in a mixture of hydrochloric acid and nitric acid (3:1) at a liquid-to-solid ratio of 50% for 10 hours, filtered and dried, and the silicon slag and quaternary ammonium base mixture was weighed according to a molar mass ratio of alkali to silicon of 2.5:1, and placed in an aqueous solution at a liquid-to-solid ratio of 10:1. The temperature was raised to 100°C, reacted for 3 hours, filtered, and the filtrate was distilled and dried. The dried solid was placed in a tubular furnace under a nitrogen atmosphere and heated at 1200°C for 2 hours. Finally, the calcined solid was taken out.

[0031] Example 7 The high silicon slag was soaked in a mixture of hydrochloric acid and nitric acid (3:1) at a liquid-to-solid ratio of 50% for 10 hours, filtered and dried, the silicon slag and quaternary ammonium base mixture were weighed according to the molar mass ratio of alkali to silicon of 2.5:1, and then 0.2% of polyethylene glycol by mass of the high silicon slag and quaternary ammonium base mixture was added, and placed in an aqueous solution at a liquid-to-solid ratio of 10:1, the temperature was raised to 100°C, the reaction was carried out for 3 hours, filtered, the filtrate was distilled and dried, the dried solid was placed in a tubular furnace under a nitrogen atmosphere, heated at 1200°C for 2 hours, and finally the calcined solid was taken out.

[0032] Comparative Example 1 Soak high silicon slag in a mixture of hydrochloric acid and nitric acid (3:1) at a liquid-to-solid ratio of 50% for 10 hours, filter and dry, weigh silicon slag and sodium hydroxide according to a molar mass ratio of alkali to silicon of 2.5:1, place them in an aqueous solution at a liquid-to-solid ratio of 10:1, raise the temperature to 100°C, react for 3 hours, filter, and distill the filtrate to dryness. Place the dried solid in a tubular furnace under a nitrogen atmosphere and heat at 1200°C for 2 hours, and finally take out the calcined solid.

[0033] Comparative Example 2 The high silicon slag was soaked in a mixture of hydrochloric acid and nitric acid (3:1) at a liquid-to-solid ratio of 50% for 10 hours, filtered and dried, and the silicon slag and quaternary ammonium base mixture was weighed according to a molar mass ratio of alkali to silicon of 2.5:1, and placed in an aqueous solution at a liquid-to-solid ratio of 10:1. The temperature was raised to 100°C, reacted for 3 hours, filtered, and the filtrate was distilled and dried. The dried solid was placed in a tubular furnace under air atmosphere and heated at 1200°C for 2 hours. Finally, the calcined solid was taken out.

[0034] Comparative Example 3 Soak high silicon slag in a mixture of hydrochloric acid and nitric acid (3:1) at a liquid-to-solid ratio of 50% for 10 hours, filter and dry, weigh silicon slag and tetraethylammonium hydroxide according to a molar mass ratio of alkali to silicon of 2.5:1, place them in an aqueous solution at a liquid-to-solid ratio of 10:1, raise the temperature to 100°C, react for 3 hours, filter, and distill the filtrate to dryness. Place the dried solid in a tubular furnace under a nitrogen atmosphere and heat at 1200°C for 2 hours, and finally take out the calcined solid.

[0035] Comparative Example 4 The high silicon slag was soaked in a mixture of hydrochloric acid and nitric acid (3:1) at a liquid-to-solid ratio of 50% for 10 hours, filtered and dried, silicon slag and tetrabutylammonium hydroxide were weighed according to the molar mass ratio of alkali to silicon of 2.5:1, placed in an aqueous solution at a liquid-to-solid ratio of 10:1, the temperature was raised to 100°C, reacted for 3 hours, filtered, and the filtrate was distilled and dried. The dried solid was placed in a tubular furnace under a nitrogen atmosphere and heated at 1200°C for 2 hours, and finally the calcined solid was taken out.

[0036] Comparative Example 5 The high silicon slag was soaked in a mixture of hydrochloric acid and nitric acid (3:1) at a liquid-to-solid ratio of 50% for 10 hours, filtered and dried, silicon slag and tetramethylammonium hydroxide were weighed according to the molar mass ratio of alkali to silicon of 2.5:1, placed in an aqueous solution at a liquid-to-solid ratio of 10:1, the temperature was raised to 100°C, reacted for 3 hours, filtered, and the filtrate was distilled and dried. The dried solid was placed in a tubular furnace under a nitrogen atmosphere and heated at 1200°C for 2 hours, and finally the calcined solid was taken out.

[0037] Comparative Example 6 The high silicon slag was soaked in a mixture of hydrochloric acid and nitric acid (3:1) at a liquid-to-solid ratio of 50% for 10 hours, filtered and dried, and the silicon slag and quaternary ammonium base mixture was weighed according to a molar mass ratio of alkali to silicon of 2.5:1, and placed in an aqueous solution at a liquid-to-solid ratio of 10:1. The temperature was raised to 100°C, reacted for 3 hours, filtered, and the filtrate was distilled and dried. The dried solid was placed in a tubular furnace under a nitrogen atmosphere and heated at 1200°C for 2 hours. Finally, the calcined solid was taken out.

[0038] The porous silicon carbon obtained by Examples 1-6 of the present invention is used as an electrode material, and its electrochemical performance test results are as follows: Table 1

[0039] From the experimental data of Examples 1-7, it can be seen that the addition of polyethylene glycol in Example 7 can improve the reactivity of silicon slag, increase the reaction rate, and the prepared porous silicon-carbon material has better electrochemical performance. In Comparative Example 1, no quaternary ammonium base is involved in the reaction, and the prepared product has no electrochemical performance after testing; the material prepared in Comparative Example 2 using oxygen as the calcination atmosphere also has no electrochemical performance after testing; the electrochemical performance of Comparative Examples 3-5 is excellent without the addition of the quaternary ammonium base mixture; The technical solution of the present invention is explained through the above embodiments, but the present invention is not limited to the above embodiments, that is, it does not mean that the present invention must rely on the above specific embodiments to be implemented. Any improvements made by technicians in the relevant field based on the present invention, or equivalent replacement of the materials selected by the present invention, etc., fall within the scope of protection of the patent.

Claims

1. A method for preparing a porous negative electrode material derived from high silicon slag, characterized in that: The method comprises the following steps: (1) Mix high silicon slag and organic matter in a certain liquid-solid ratio in a solution and react at a certain temperature: (2) After the reaction is completed, filter and take the filtrate; (3) Evaporating and crystallizing the filtrate; (4) The crystalline product is calcined to prepare a silicon-based negative electrode material.

2. The method for preparing a porous negative electrode material derived from high silicon slag according to claim 1, characterized in that: High silicon slag composition: silicon dioxide 68%-69%, silicate 15.5%-16.5%, basic calcium phosphate dihydrate 14.5%-15.5%, potassium fluoride 0.5%-1%.

3. The method for preparing a porous negative electrode material derived from high silicon slag according to claim 1, characterized in that: The high silicon slag is firstly pickled, and the pickling solution comprises a mixture of one or more of nitric acid, hydrochloric acid and sulfuric acid, and the mass concentration of the pickling solution is 30-50%.

4. The method for preparing a porous negative electrode material derived from high silicon slag according to claim 1, characterized in that: The organic substance is a quaternary ammonium base.

5. The method for preparing a porous negative electrode material derived from high silicon slag according to claim 4, characterized in that: The quaternary ammonium base is a mixture of tetramethylammonium hydroxide, tetraethylammonium hydroxide and tetrabutylammonium hydroxide.

6. The method for preparing a porous negative electrode material derived from high silicon slag according to claim 5, characterized in that: The molar ratio of quaternary ammonium alkali to silicon in step (1) is (1.8-3):1, the reaction temperature is 50°C-100°C, and the liquid-to-solid ratio is 5-20.

7. The method for preparing a porous negative electrode material derived from high silicon slag according to claim 6, characterized in that: The molar ratio of tetramethylammonium hydroxide, tetraethylammonium hydroxide and tetrabutylammonium hydroxide in the quaternary ammonium base mixture in step (1) is (0.1-2): (0.1-2): (0.1-2).

8. The method for preparing a porous negative electrode material derived from high silicon slag according to claim 7, characterized in that: Polyethylene glycol is also added to the mixture of high silicon slag and quaternary ammonium alkali, and the added proportion is 0.1%-0.5% of the total mass of the mixture of high silicon slag and quaternary ammonium alkali.

9. The method for preparing a porous negative electrode material derived from high silicon slag according to claim 1, characterized in that: The reaction time of step (2) is 1-5h.

10. The method for preparing a porous negative electrode material derived from high silicon slag according to claim 1, characterized in that: Step (4) The calcination atmosphere is nitrogen, the calcination temperature is 700°C-1000°C, and the calcination time is 1-3h.

Citation Information

Patent Citations

  • A doped and coated spherical silicon-carbon negative electrode material, preparation method and use thereof

    CN117894968B

  • Titanium silicalite molecular sieve with MFI structure and preparation method thereof

    CN103708493A

  • Preparation method of ultrapure silica sol and product thereof

    CN114804122A

  • Electrodeposition three-dimensional silicon composite negative electrode material and preparation method thereof

    CN115939338A

  • Process for treating silicon slag

    CN1326821A